Zomato Gold : the logout campaign - Roy, Debjit; Garg, Amit; Govil, Eshaan (London : Indian Institute of Management, Ahmedabad, 2020)
Since 2008, Zomato, a food-tech company, has been operating in India. It started as a restaurant search and discovery platform on which a restaurant could advertise itself. It now operated in food delivery, loyalty programmes, and delivered cooking essentials to restaurants. Zomato oversold its Gold membership and offered massive discounts on Zomato Gold and online food delivery. The discounts offered by Zomato triggered resistance from the restaurant owners culminating in their "Log out campaign." The Logout Campaign led to Zomato re-assessing its growth strategies.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business planning -- Case studies; Pricing -- Case studies; Advertising -- Case studies